2018
DOI: 10.3390/en11092445
|View full text |Cite
|
Sign up to set email alerts
|

Development of Economizer Control Method with Variable Mixed Air Temperature

Abstract: Achieving energy efficiency by improving the operating method of the system used in existing buildings is attracting considerable attention. The Building Design Criteria for Energy Saving was established to induce energy saving design in the domestic construction field, and the introduction of a free-cooling system, such as an economizer system, as an item of the mechanical sector, was evaluated. The economizer is an energy saving method that reduces the building load by introducing outdoor air through damper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Lee et al confirmed that the set value of the mixed air temperature that consumes the minimum energy according to the load is not constant when controlling the economizer dry-bulb temperature in constant air volume (CAV) single duct system. Based on this, a control method for resetting the mixed air temperature set value according to the load was proposed [10]. Likewise, many studies on economizer control setpoints are being conducted, but there is a lack of studies on set-points considering real-time weather and HVAC system load conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al confirmed that the set value of the mixed air temperature that consumes the minimum energy according to the load is not constant when controlling the economizer dry-bulb temperature in constant air volume (CAV) single duct system. Based on this, a control method for resetting the mixed air temperature set value according to the load was proposed [10]. Likewise, many studies on economizer control setpoints are being conducted, but there is a lack of studies on set-points considering real-time weather and HVAC system load conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al analyzed the relationship between the mixed-air temperature and energy consumption using the BIN method and a simulation; it was confirmed that the set point value of the mixed-air temperature at which energy consumption was minimized was not constant depending on the operating conditions. Accordingly, an optimal economizer control that adjusts the mixed-air temperature variable according to the load using an ANN (Artificial Neural Network) was presented [10] As such, the economizer is an energy-saving operation method, and the mixed air temperature set-point is controlled constantly in the existing control. Although various studies have been conducted on the control of economizers, there is insufficient research dealing with economizer optimal control that control the mixed air temperature set-point in consideration of real-time dynamic conditions (outdoor air condition, indoor occupancy etc.)…”
Section: Introductionmentioning
confidence: 99%